CLASSROOM INTERACTION IN ENGLISH LANGUAGE INSTRUCTION USING FLINT SYSTEM AS THE BASIS OF ANALYSIS IN RELATION TO STUDENT’S COMPETENCY AT ELEVENTH GRADE IN SMA N 4 SINGARAJA - ., Wisnu Saputra; ., Drs.Gede Batan,MA; ., Putu Eka Dambayana S., S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk menemukan kategori dari interaksi kelas yang terjadi di kelas sebelas SMA N 4 Singarja berdasarkan Foreign Language Interaction Analysis (FLINT) System, kategori yang paling sering muncul, dan level dari kompetensi siswa setelah proses belajar mengajar. Subjek dari penelitian ini adalah dua orang guru dan siswa di kelas XI MIA 2 dan XI MIA 3. Peneliatian ini dirancang menggunakan penelitian deskriptif kualitatif. Hasil dari penelitian menjunjukkan bahwa: (1) seluruh kategori dari interaksi kelas berdasarkan FLINT system ditemukan selama proses belajar mengajar. Kategori-kategori kersebut adalah Deals with Feeling, Praise and Encourages, Jokes, Uses Ideas of Student, Repeats Student Response Verbatim, Asks questions, Gives information, Corrects without Rejection, Gives Direction, Direct Pattern Drills, Criticizes Student Behavior, Criticizes Student Response, Student Response Specific, Student Response Choral, Student Response Open-Ended or Student Initiated, Silence, Silence AV, Confusion Work-Oriented, Confusion non work-oriented, Laughter, Uses of Native Language and Nonverbal. (2) Kategori dari teacher talk yang sering terjadi adalah asking question sedangkan kategori dari student talk yang sering muncul adalah student response, open ended or student initiated. (3) rata-rata nilai dari kompetensi siswa dari seluruh observasi adalah 79. Itu berarti kategori dari nilai tersebut adalah B-. Walaupun hasil dari observasi menujukkan bahwa student talk lebih dari teacher talk, namun penggunaan bahasa ibu sangat sering digunakan ketika observasi.Kata Kunci : Foreign Language Interaction (FLINT) system, Interaksi Kelas, Kompetensi Bahasa Inggris, Pembelajaran Bahasa Inggris This study aimed at finding the classroom interaction categories occurring in the eleventh grade of SMA N 4 Singaraja based on Foreign Language Interaction Analysis (FLINT) System, category which most frequently occurred, and level of the student’s competency after teaching and learning process. The subjects of the study were two teachers and students in XI MIA 2 and XI MIA 3. This study was designed by using descriptive qualitative research. The result of the research shows that: (1) all categories of classroom interaction based on FLINT system exist during the teaching learning process. Those are Deals with Feeling, Praise and Encourages, Jokes, Uses Ideas of Student, Repeats Student Response Verbatim, Asks questions, Gives information, Corrects without Rejection, Gives Direction, Direct Pattern Drills, Criticizes Student Behavior, Criticizes Student Response, Student Response Specific, Student Response Choral, Student Response Open-Ended or Student Initiated, Silence, Silence AV, Confusion Work-Oriented, Confusion non work-oriented, Laughter, Uses of Native Language and Nonverbal. (2) The teacher talk category that mostly occurs is asking question while student talk category that mostly appears is student response, open ended or student initiated (3) the average score of the students’ competency from all of the observation is 79. It means the category of the average score was B-. Even the result of all the observation shows that the students talk more than the teacher talk, but the use of native language is very highly used in the observation.keyword : Classroom interaction, English Language Instruction, English Language Competency, Foreign Language Interaction (FLINT) system